(untitled) (Development Service Industry Management, 2024)
The article is devoted to the analysis of the possibilities of applying a process-innovative approach to the design and construction of restaurant enterprises using modern software tools of the automated design and calculation system and the automated system of managing the building complex. The need to carry out complex technological calculations to determine the optimal location and size of the premises of the restaurant business actualizes the study of the possibilities of using a process approach to design and construction. It was found that the processes of design and construction of restaurant enterprises include solving a number of complex construction tasks. It is proposed to organize design and construction works using a process approach, which is based on a systemic vision of the construction object and ensures the functional orientation of design and construction processes. It is shown that the use of innovative technologies of information modeling of buildings, CAD and ASUB optimizes the design and construction processes by maximizing the efficiency of the use of information flows and creating a data bank for the design and construction of the object. It has been proven that the use of modern software allows for the formation of finished conceptual solutions with modeling visualization. It is proposed to conceptualize the design in the ArchiCAD environment to take into account suggestions for constructability, cost optimization, and the selection of building materials. It is shown that analytical modeling allows engineers to interact with virtualized models to introduce conceptual characteristics of a construction object. It was found that the volume-planning solution fully corresponds to the functional purpose of the restaurant enterprise, and the constructive solutions of the building provide technological and economic requirements for the effective operation of the designed object. It is advisable to carry out further research in the direction of the development of automated information systems for the management of design and construction developments and the development of the national Bank of innovative design and construction solutions.